LEGAL GUARANTEES FOR THE PROTECTION OF PROPERTY RIGHTS IN THE REPUBLIC OF UZBEKISTAN - Dilorom Mamirovna Karakhodzhaeva (American Journals, 2023)
The essence and meaning, the main legal guarantees for the protection of property rights in the Republic of Uzbekistan, as well as the problems of expanding the ways and means of protecting property rights in the view of modern science are characterized.
Keywords: Political guarantees, economic guarantees, legal guarantees, property rights, entrepreneurship, protection of property rights.